2022
DOI: 10.1111/jog.15208
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile vessel at the posterior bladder wall: A new sonographic marker for placenta percreta

Abstract: Objective: We investigated using "pulsatile vessels at the posterior bladder wall" as a novel sonographic marker to demonstrate the severity of placenta accreta spectrum (PAS). Methods: This observational case-control study of 30 pregnant women was performed at Hackensack Meridian Health's Center for Abnormal Placentation in 2020. The case group was made up of women with historically described sonographic signs of PAS and was compared against two control groups: (1) women with uncomplicated placenta previa and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These comprised loss of the ‘clear zone’ (hypoechoic retroplacental zone), myometrial thinning, bladder‐wall interruption, presence of a placental bulge, uterovesical hypervascularity, placental lacunae and bridging vessels. None of the eight new signs identified in the present systematic review 14–28 reached a predefined consensus threshold as ultrasound findings that increase the probability of PAS at birth (Table 1). In addition, the panel was queried about second‐ or third‐trimester ultrasound findings that are not specific for PAS (i.e.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These comprised loss of the ‘clear zone’ (hypoechoic retroplacental zone), myometrial thinning, bladder‐wall interruption, presence of a placental bulge, uterovesical hypervascularity, placental lacunae and bridging vessels. None of the eight new signs identified in the present systematic review 14–28 reached a predefined consensus threshold as ultrasound findings that increase the probability of PAS at birth (Table 1). In addition, the panel was queried about second‐ or third‐trimester ultrasound findings that are not specific for PAS (i.e.…”
Section: Resultsmentioning
confidence: 92%
“…After exclusion of duplicates and two articles that were not available, 880 remained, of which a further 793 were excluded after screening the titles and abstracts, as the data they reported were not relevant. The remaining 87 studies were retrieved for full-text review, of which 72 were excluded after in-depth review, leaving 15 studies describing eight new ultrasound signs for the prenatal evaluation of PAS [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The process of selection of these articles is summarized in Figure S1, and the characteristics of the 15 studies identified by the systematic review are presented in Table S1.…”
Section: Literature Searchmentioning
confidence: 99%